Early diagnosis of amyotrophic lateral sclerosis by threshold tracking and conventional transcranial magnetic stimulation. (22nd July 2021) - Tankisi, Hatice; Nielsen, Christina S.‐Z.; Howells, James; Cengiz, Bülent; Samusyte, Gintaute; Koltzenburg, Martin; Blicher, Jakob U.; Møller, Anette T.; Pugdahl, Kirsten; Fuglsang‐Frederiksen, Anders; de Carvalho, Mamede; Bostock, Hugh
Abstract: Background and purpose: Short‐interval intracortical inhibition by threshold tracking (T‐SICI) has been proposed as a diagnostic tool for amyotrophic lateral sclerosis (ALS) but has not been compared directly with conventional amplitude measurements (A‐SICI). This study compared A‐SICI and T‐SICI for sensitivity and clinical usefulness as biomarkers for ALS. Methods: In all, 104 consecutive patients referred with suspicion of ALS were prospectively included and were subsequently divided into 62 patients with motor neuron disease (MND) and 42 patient controls (ALS mimics) by clinical follow‐up. T‐SICI and A‐SICI recorded in the first dorsal interosseus muscle (index test) were compared with recordings from 53 age‐matched healthy controls. The reference standard was the Awaji criteria. Clinical scorings, conventional nerve conduction studies and electromyography were also performed on the patients. Results: Motor neuron disease patients had significantly reduced T‐SICI and A‐SICI compared with the healthy and patient control groups, which were similar. Sensitivity and specificity for discriminating MND patients from patient controls were high (areas under the receiver operating characteristic curves 0.762 and 0.810 for T‐SICI and A‐SICI respectively at 1–3.5 ms). Paradoxically, T‐SICI was most reduced in MND patients with the fewest upper motor neuron (UMN) signs (Spearman ρ = 0.565, p = 4.3 × 10 −6 ). Conclusions: Amplitude‐based measure of cortical inhibition and T‐SICI are both sensitive measures for the detection of cortical involvement in MND patients and may help early diagnosis of ALS, with T‐SICI most abnormal before UMN signs have developed. The gradation in T‐SICI from pathological facilitation in patients with minimal UMN signs to inhibition in those with the most UMN signs may be due to progressive degeneration of the subset of UMNs experiencing facilitation. Abstract : In 104 patients referred with suspicion of ALS, two methods of recording short‐interval intracortical inhibition (SICI) detected cortical involvement with high sensitivity and specificity. The new method of threshold‐tracking SICI (T‐SICI) was paradoxically most reduced in the patients with fewest upper motor neuron signs, suggesting facilitation in a subset of cortical neurons which subsequently degenerate.